Strategi Peningkatan Kualitas Pendidikan Kelas Homogen di MTs Darussalam Krempyang Tanjunganom Nganjuk - M. Yusuf; Abdul Kholiq; Muhammad Zainul Mahya (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2022)
In the world of education, there are several ways that can be used to improve the quality of education, both in the type of homogeneous class or heterogeneous class. Homogeneous class is a class which in its learning is only occupied by students from the same gender background, so of course certain steps are needed to support the quality of education. MTs Darussalam Krempyang Tanjunganom Nganjuk uses homogeneous classroom management as a strategy to improve the quality of education. The focus of the study in this study is how to improve the quality of homogeneous classroom education at MTs Darussalam Krempyang Tanjunganom Nganjuk and its supporting and inhibiting factors. This study uses a qualitative approach with data collection in the form of observation, interviews and documentation. The data analysis technique is through the stages of presentation, data reduction, and verification. For the validity of the data, the authors used the technique of triangulation of sources, reference materials, and peer checks. The results of this study indicate that the strategy used in the target object is to improve the quality of homogeneous classroom education, the school combines various methods related to learning that touches the academic and non-academic sides, as well as collaborates with the cottage and extracurricular development while taking into account the supporting and inhibiting factors